Enhanced single-ion magnetic and ferroelectric properties of mononuclear Dy(iii) enantiomeric pairs through the coordination role of chiral ligands. Issue 28 (24th March 2017) - Li, Xi-Li; Hu, Ming; Yin, Zhigang; Zhu, Cancan; Liu, Cai-Ming; Xiao, Hong-Ping; Fang, Shaoming
Abstract : Mononuclear Dy(iii ) enantiomeric pair with coordinated chiral ligands exhibit enhanced single-ion magnet, ferroelectric and chiroptical properties with respect to the other one with protonated chiral ligands. Abstract : The structures and properties of two mononuclear Dy(iii ) enantiomeric pairs were dramatically controlled by crystallization temperature; the enantiomeric pair with coordinated chiral N, N ′-donor ligands exhibits enhanced single-ion magnetic, ferroelectric and chiroptical properties with respect to the other one with protonated chiral N, N ′-donor ligands.